The Role of Conventional Chest X-Ray in Detection and Evaluation of Long COVID-19 - Andri; Yuanita Amanda (PT Kalbe Farma Tbk., 2022)
A 52-year-old woman came to ER with shortness of breath, fever, and cough with oxygen saturation of 80% on room air. The COVID-19 PCR test was positive. CXR showed it infiltrates ground-glass opacities in both lungs and cardiomegaly. Chest X-ray at discharge from the hospital showed decreased infiltrate and fibrosis in two lung. She came to the ER 4 days later with worsened shortness of breath. CXR showed diffuse infiltrates in both lungs and cardiomegaly. Discussion: COVID-19 patients can develop long-term sequelae and complications (long COVID-19). Although CT is now considered the primary investigation for COVID-19, CXR is still valid for detecting and monitoring its progression. Conclusion: CXR is useful for detecting and monitoring the rapid advancement of lung abnormalities in long COVID-19. Wanita 52 tahun datang ke IGD dengan sesak napas, demam, batuk; dengan saturasi oksigen 80% udara ruangan. Tes PCR COVID-19 positif. Rontgen toraks menunjukkan infiltrat di kedua lapangan paru, ground glass opacities, dan kardiomegali. Rontgen toraks saat keluar rumah sakit menunjukkan penurunan gambaran infiltrat dan fibrosis pada dua lapangan paru. Empat hari setelah keluar rumah sakit pasien kembali sesak napas. Rontgen toraks menunjukkan infiltrat difus dikedua paru dan kardiomegali. Diskusi: Pasien COVID-19 dapat mengalami sekuele jangka panjang dan komplikasi, disebut long COVID-19. Walaupun CT-scan menjadi pendeteksi utama COVID-19, rontgen toraks masih bermanfaat untuk memantau progresi sindrom tersebut. Simpulan: Rontgen toraks berguna untuk deteksi dan memantau kelainan paru pada long COVID-19.